Environmental protection and labor market composition - Jaiswal, Sreeja; Balietti, Anca; Schäffer, Daniel (AWI discussion paper series, 2023)
This paper investigates the long-term impacts of protected area management on the labor market participation and composition of the affected population. We study changes spanning two decades in the Western Ghats region of India, one of the key global biodiversity hotspots with the highest population density. Our findings indicate a noteworthy shift toward non-farm employment. Additionally, our research unveils a marked trend towards irregular income patterns: eco-development initiatives appear to have resulted in a significant decline in year-round employment coupled with a corresponding rise in employment for less than six months a year. The primary mechanism we identify is a distinct change in land use patterns, whereby villages under the scope of eco-development initiatives manifest a substantial transition from irrigated to rainfed agricultural land, known to be conducive to seasonal employment. Following these changes, lower consumption levels and higher poverty rates persist in the affected population compared to surrounding areas.
Keywords: Graue Literatur